Is That a Rhetorical Question? Shipwrecked Sailor (pHermitage 1115), 150 Reconsidered - Scalf, Foy (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
This article examines a difficult passage from the Tale of the Shipwrecked Sailor (pHermitage 1115, 150). Near the end of the story, the official relates the good deeds which will be performed on behalf of the divine snake if he allows the official to return home. The snake’s enigmatic response has provoked a variety of interpretations. It may be possible to resolve the questions surrounding this section of the tale by understanding the passage as a rhetorical question used by the snake to trump the official.